2007
DOI: 10.3748/wjg.13.5985
|View full text |Cite
|
Sign up to set email alerts
|

Updates on abdominal desmoid tumors

Abstract: Desmoid tumor is a monoclonal, fibroblastic proliferation arising in musculoaponeurotic structures. This connective tissue hyperplasia infiltrates locally, recurs frequently after resection but does not metastasize. Abdominal desmoid occurs sporadically, in association with some familial syndromes and often represents a clinical dilemma for surgeons. The enigmatic biology and anatomical location of abdominal desmoids make treatment recommendations difficult. This distinct pathological entity is reviewed with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…The role of imaging is to defi ne the degree of extension to local structures and to establish the tumor relationship to the neurovascular structure. 15 As our patient had no clinical or familial signs of FAP, locoregional recurrence of colon cancer was the assumed diagnosis. Although systemic chemotherapy before surgical resection might have been a treatment option, we considered that surgical resection to confi rm pathology was mandatory before the induction of systemic chemotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…The role of imaging is to defi ne the degree of extension to local structures and to establish the tumor relationship to the neurovascular structure. 15 As our patient had no clinical or familial signs of FAP, locoregional recurrence of colon cancer was the assumed diagnosis. Although systemic chemotherapy before surgical resection might have been a treatment option, we considered that surgical resection to confi rm pathology was mandatory before the induction of systemic chemotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…Despite complete resection with negative microscopic margins, desmoid tumors have recurrence rate of about 40% [1,22,23]. It is therefore suggested that surgery should be performed only when absolutely necessary [9].…”
Section: Discussionmentioning
confidence: 97%
“…Individuals in the age group of 15–60 years can be affected; desmoids are rare in the young and in the elderly [68], more common in women than in men [2], and have no significant racial or ethnic predilection.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-abdominal desmoids are often observed in FAP (3.5–32%) and Gardner's syndrome or following abdominal trauma (surgical or nonsurgical) [6]. The association between antecedent trauma and the development of desmoids may be related to a possible molecular connection between wound-healing processes and fibroproliferative disorders of mesenchymal tissue [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation